1992
DOI: 10.1007/bf01473534
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to neural networks and their applications in manufacturing

Abstract: It is a frequently quoted fact that today's manufacturing functions are becoming more and more 'inter-disciplinary', with new approaches and techniques continuously and rapidly introduced and adopted. The recent applications of neural networks in manufacturing provide a typical example of this trend. This paper examines the structures and functions of neural networks, and provides some examples of their manufacturing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…We observe that words with similar semantic meaning are closer in the word embedding space, e.g., {run, walk, move}, whereas words having different semantic meaning are far, e.g., run and eat. In Natural Language Processing (NLP), researchers use techniques such as neural network [64] and co-occurrence matrix [43] to project words onto a k-dimensional vector space, and words appearing in similar textual contexts get closer embedding in the vector space. One of the most popular method to extract word embedding from a large scale corpus is Word2Vec [38], which uses a two layer neural network to predict the surrounding words of a target word.…”
Section: Word Embeddingmentioning
confidence: 99%
“…We observe that words with similar semantic meaning are closer in the word embedding space, e.g., {run, walk, move}, whereas words having different semantic meaning are far, e.g., run and eat. In Natural Language Processing (NLP), researchers use techniques such as neural network [64] and co-occurrence matrix [43] to project words onto a k-dimensional vector space, and words appearing in similar textual contexts get closer embedding in the vector space. One of the most popular method to extract word embedding from a large scale corpus is Word2Vec [38], which uses a two layer neural network to predict the surrounding words of a target word.…”
Section: Word Embeddingmentioning
confidence: 99%
“…Per their report, the neural networks were capable of detecting tool condition accurately. Wu (1992) developed a neural network model to detect tool failure based on the level of cutting force and vibration or acoustic emission. Brophy et al (2002) proposed a two-stage neural network model to detect anomalies in the drilling process.…”
Section: Condition Monitoringmentioning
confidence: 99%
“…ANNs have been used to solve numerous problems associated with manufacturing operations. Application of ANN in manufacturing system design [2]- [6], manufacturing process control [7], robot scheduling [8], industrial pattern recognition [9], and manufacturing operational decision [10] is reported.…”
Section: Introductionmentioning
confidence: 99%